How to bring science and sports practice together: a case project - Mulder, R. C. M.; Rykkje, B. (Nordic Winter Sports Conference, 2020)
In long-track speed skating, the performance of an athlete is determined by finish time. Coaches therefore use a lot of their time manually timing their athletes during training sessions to get an indication of performance. An experienced stopwatch user provides relatively accurate timing results, but generally cannot log data and give split times of all athletes during a training session.